A case of esophageal carcinoma due to esophageal squamous papillomatosis - Fraga, E. (2020)
tINTRODUCTION: Squamous Papilloma is a rare benign tumor of the esophagus. Esophageal squamouspapilloma is thought to arise from a chronic inflammatory reaction due to mechanical or chemical irri-tant. ESP is usually considered to have a benign clinical course; however, some reports highlight thepotential development of a malignancy. The development of extensive esophageal squamous papillomasalso known as squamous papillomatosis of the esophagus is even less frequent.PRESENTATION OF THE CASE: We present the case of an esophageal papillomatosis that developed intoan invasive esophageal squamous cell carcinoma that was only diagnosed in the surgical specimen afterminimally invasive Ivor-Lewis esophagectomy and in this case report, we discuss its etiology, diagnosisand treatment.CONCLUSION: Extensive papillomatosis with continuous symptoms, especially persistent dysphagia,should always prompt a thorough analysis into a possible underlying malignancy.